Studi Takhrīj Hadis Tentang Kelembutan dalam Keluarga: Takhrīj Hadith Study About Gentleness in Family - Nuraeni Novira; Maryam, Maryam; Asnawati Patuti (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This research discusses the study of takhrij hadith regarding tenderness in the family. This research is descriptive research using library methods and approaches to the study of takhrij hadith, normative and historical. The literary sources used are the Musnad Ahmad ibn Hanbal Book as a primary source. The results of this research are the quality of the hadith narrated by Ahmad ibn Hanbal No. 24,427 regarding a gentle attitude in the family is a sign of good quality and is valid, this is reflected in the results of the takhrij carried out. A family that is filled with various goodness or happiness means that Allah has indeed given tenderness to that family, or it could be the other way around, because of the tenderness that exists in the family, a family gets various goodness that keeps it intact, harmonious and meaningful.